Protected areas do not outperform urban wastelands in supporting insect pollinators and pollination in central Germany - Panagiotis Theodorou; Wilhelm H.A. Osterman; Janna H. Mrozek; Bilyana S. Wild; Michael Beckmann; Julia Osterman; Robert J. Paxton (Basic and Applied Ecology)
The Natura 2000 network is central to Europe's conservation efforts to address biodiversity decline, with ongoing plans to expand protected areas and restore habitats across the European Union. However, due to the relative scarcity of biodiversity assessments within Natura 2000 sites, our understanding of how effective these areas are at protecting biodiversity and how they can be improved remains limited. At the same time, urban green spaces and associated disturbed, unmanaged vacant areas, also known as urban wastelands, have gained attention as potential conservation targets due to their high insect species richness. Here, we assess and compare the biodiversity of pollinators within Natura 2000 reserves and urban wastelands to evaluate their relative value for biodiversity protection and pollination services. To achieve this, we compared pollinator communities, their flower-visitation patterns and pollination services using potted experimental plants in flower-rich Natura 2000 sites and paired non-protected, unmanaged, yet similarly flower-rich urban wastelands. While the total biomass and overall abundance of insects did not differ between the two habitat types, wild bee abundance and richness were higher in urban wastelands, whereas pollinator communities were more heterogeneous among Natura 2000 sites. Though insect flower-visitation network metrics were similar across both habitats, seed set of experimental plants was higher in urban wastelands compared to Natura 2000 sites, indicating lower pollination services in the nature reserves. Our findings suggest that while Natura 2000 areas contained unique biodiversity compared to urban wastelands, the current status of protected areas in Germany is inadequate to conserve biodiversity hotspots for bees, including endangered species and the pollination services they provide. We highlight the potential for urban areas to support biodiversity conservation as well as the need to develop targeted strategies for bee conservation in Natura 2000 areas.